Analisis Implementasi Penggunaan Media Visual Sebagai Sarana Penyampaian Lesson Learned Bagi Operator Di Pt Terminal Teluk Lamong Surabaya - Cinta Lasya; Nanik Hariyana (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Communication of occupational safety information to workers, particularly operators working in the field, is an important aspect that must be given attention to ensure safe and smooth work processes. The problem addressed in this study is the suboptimal understanding among operators regarding work procedures, as well as occupational health and safety aspects in the port environment, which are crucial and require serious attention. This study aims to examine how visual media is used as a tool for conveying lesson learned to operators at PT Terminal Teluk Lamong, analyze the factors influencing the optimization of visual media in enhancing operator comprehension, and evaluate the impact of visual media on operator compliance with work procedures and operational success. This research adopts a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation related to the implementation of visual media in the workplace. The analysis was conducted through three main stages of qualitative research: description, data reduction, and data selection, in order to gain a deep understanding of the studied phenomenon. The results show that visual media such as infographics and educational videos are effective in helping operators better understand and remember work procedures. The optimization of visual media is influenced by content design, regular updates of materials, strategic placement of the media, and operator involvement in providing feedback. In addition, the use of visual media has a positive impact on improving operator compliance with overall occupational safety.